Ribosome-induced RNA conformational changes in a viral 3′-UTR sense and regulate translation levels. Issue 1 (December 2018) - Hartwick, Erik; Costantino, David; MacFadden, Andrea; Nix, Jay; Tian, Siqi; Das, Rhiju; Kieft, Jeffrey
Abstract Structured RNA elements, programmed RNA conformational changes, and interactions between different RNA domains underlie many modes of regulating gene expression, mandating studies to understand the foundational principles that govern these phenomena. Exploring the structured 3′ untranslated region (UTR) of a viral RNA, we discovered that different contexts of the 3′-UTR confer different abilities to enhance translation of an associated open reading frame. In one context, ribosome-induced conformational changes in a 'sensor' RNA domain affect a separate RNA 'functional' domain, altering translation efficiency. The structure of the entire 3′-UTR reveals that structurally distinct domains use a spine of continuously stacked bases and a strut-like linker to create a conduit for communication within the higher-order architecture. Thus, this 3′-UTR RNA illustrates how RNA can use programmed conformational changes to sense the translation status of an upstream open reading frame, then create a tuned functional response by communicating that information to other RNA elements. Complex RNA three-dimensional structures undergo functionally important programmed conformational changes. Here, the authors report how two structurally and functionally coupled RNA domains within a viral 3′-UTR sense the ribosome through conformational changes and respond by modulating translation.